2020
DOI: 10.4038/joshhm.v6i0.95
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Vulnerabilities of Youth Towards STIs and HIV Infection; A Cross Sectional Study among Youth Attending ‘Youth Corps Centres’ in Western Province of Sri Lanka

Abstract: Introduction:Youth is the period where individuals transform from dependent childhood to independent adults. The incidence of Sexually Transmitted Infections (STI) and HIV among youth in Sri Lanka, is rising.Objective: To assess the risk behaviours and vulnerabilities towards Sexually Transmitted Infections and HIV among youth attending youth corps centres in the Western province of Sri Lanka. Method:A descriptive cross sectional study was carried out using a self-administered questionnaire among the trainees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…The same study revealed that the trainee's STI knowledge was positively associated with age, education level, and wealth quintile. Similar to the present study this study also indicated a significant difference in knowledge across the ethnic and religious categories [22].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The same study revealed that the trainee's STI knowledge was positively associated with age, education level, and wealth quintile. Similar to the present study this study also indicated a significant difference in knowledge across the ethnic and religious categories [22].…”
Section: Discussionsupporting
confidence: 90%
“…However, the study carried out among youth corps trainees in Western province indicated that only 34% of the youth have ever used a condom, while 32% didn't know where to go for a condom. The same study also reports that 51% of the youth did not want to use a condom in future sexual encounters [22].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Following the National youth health survey conducted in 2012-2013, a large-scale or national level information is lacking on sexual behaviour and contraceptive youth of Sri Lanka [ 11 ]. Among the few smaller studies conducted subsequently on sexual behaviour of youth, have highlighted the rise in high-risk sexual behaviour among the youth [ 14 , 15 ]. Further, authorities have observed a recent rise of HIV/AIDS incidence among youth in Sri Lanka [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Akintade et al, (2011) in underdeveloped nations, the number of young women reporting unwanted pregnancy is high. As a developing country in South Asia, Sri Lanka also has a prevalence rate between 23-46% of unplanned pregnancies within the country (Ranatunga & Jayaratne, 2020) and the prevalence of STDs among Sri Lankan youth was found to be increasing (Batagalla & Manathunge, 2020). Poor knowledge, awareness and undesirable attitude towards contraception usage are some of the major factors associated with unintended pregnancies and transmission of sexually transmitted diseases (Semachew Kasa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%